2015
DOI: 10.1016/j.laa.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Construction of robust frames in erasure recovery

Abstract: Erasures occur often in signal transmission. In [10], the authors introduced robust frames, with which one can recover erased frame coefficients even if the locations are unknown. In this paper, we give some explicit construction of robust frames.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For example, in [13], the authors found the optimal dual frames that minimize the reconstruction error for 1-erasure and 2-erasures. Many other scholars have researched this issue in recent years, such as [14][15][16], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in [13], the authors found the optimal dual frames that minimize the reconstruction error for 1-erasure and 2-erasures. Many other scholars have researched this issue in recent years, such as [14][15][16], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that every full spark frame can be rescaled to be an almost self-located frames or almost robust frames. In their work, 11 Lv and Sun give some explicit construction of almost self-located frames and almost robust frames.…”
Section: Introductionmentioning
confidence: 99%
“…The frames constructed in Lv and Sun and Han et al 11,12 contain irrational numbers. Considering the quantization errors in application, it is necessary to discuss the stability of the property of almost self-located robustness.…”
Section: Introductionmentioning
confidence: 99%